Employing Artificial Intelligence Applications in Editing News Writing GenresChatGPT Application as a Model - Semaa Sadoon Azziz, Asst. Lect. (lark, 2025)
This research aims to identify the evaluation and attitudes of editors working in media institutions regarding the use of artificial intelligence applications, including GPT Chat, in editing news genres (news, reports, news stories). The study is descriptive and uses the survey method to answer the research questions and objectives through a purposive sample of 40 editors and academics during the period from 1/2 to 28/2/2025. A questionnaire was used as the scientific tool and distributed among editors working in media institutions and specialized academics to collect data related to the research topic. The research concluded with several key findings: employing intelligent applications helps improve the efficiency of news products in various editing stages from information gathering to final editing. Editors and academics prefer manual editing of news genres, considering intelligent applications as supportive tools rather than replacements. Artificial intelligence applications have important advantages related to saving time and effort, creativity in style, professional phrasing, and diverse information. Among the most used AI applications is the free application Chat GPT.